PENGEMBANGAN BAHAN AJAR TEMATIK BERBASIS MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING DI MADRASAH IBTIDAIYAH SWASTA - Dian Andesta Bujuri; Natasya Ananda; Agra Dwi Saputra; Tutut Handayani (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Kediri, 2022)
Teaching materials in thematic learning based on learning models are not yet available. This underlies researchers' development textbooks integrated into the Contextual Teaching and Learning (CTL) learning model. The material developed in the textbook is the theme of 3 sub-themes 1 class IV at MI Azizan Palembang. This type of research is the ADDIE model's research and development, which includes the stages of analysis, design, development, implementation, and evaluation. The research and development process that researchers carry out gets positive results. Developing thematic teaching materials based on the CTL learning model on theme 3 subtheme 1 grade 4 at MI Azizan Palembang is categorized as valid with the validation assessment of design experts 73%, linguists 75%, and very good categories on material experts 92%. The results of the responses of grade 4 students and teacher assessments in the use of teaching materials are categorized as very practical. In the group trial stage, the percentage of scores reached 93%, field trials obtained a percentage score of 90%, and teacher assessments obtained a percentage of 93%. This shows that thematic teaching materials based on the CTL learning model on theme 3 sub-theme 1 grade 4 at MI Azizan Palembang are suitable for use in the implementation of learning.